(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The present article analyzes the essence of pedagogical culture and examines its principal structural components. The study identifies axiological, cognitive, communicative, behavioral, reflective, and creative components as the main constituents of student pedagogical culture. Each component contributes to the formation of professional competence, ethical responsibility, and readiness for lifelong learning. The article emphasizes that the development of pedagogical culture among students should be considered a continuous and purposeful process implemented through educational activities, practical experiences, and reflective self-improvement. Recommendations are proposed for higher education institutions to create pedagogical conditions that facilitate the comprehensive development of students’ pedagogical culture.